Effect of Nitrogen Levels on the Growth and Yield of Two Varieties of Shallots (Allium Ascalonicum - Salim, Ceppy Nurwan; Widodo, R Wahyono; Budiasih, R (Institute of Computer Science (IOCS), 2021)
The aim of this research is to study the effect of giving a dose of Nitrogen fertilizer on the growth and yield of the onion plants of the Batu Ijo variety and the Cipanas Maja variety. The experiment was conducted in the experimental garden of the Faculty of Agriculture, University of Winaya Mukti, Tanjungsari District, Sumedang Regency with a height of 850 m above sea level from July 2018 - September 2018. The research design used was a factorial Randomized Block Design (RBD) consisting of two factors: the first factor onion (v) divided by 2 levels, namely v1 = onion variety of Batu Ijo, v2 = onion variety of Maja Cipanas, and the second factor was ZA fertilizer (n) divided by 4 levels namely n0 = 0 kg ha-1, n1 = 200 kg ha-1, n2 = 250 kg ha-1, n3 = 300 kg ha-1 is repeated 4 times. The results of the experiment showed that Nitrogen had no significant effect on growth and yield of onion of the Batu Ijo Variety and the Cipanas Maja Variety, the onion of the Cipanas Maja Variety produced higher dry tuber weights (1.62 kg / plot or 16 .17 tons /ha) than onion Batu Ijo Variety (1.41 kg/plot or 14.07 tons/ha), optimum dose of Nitrogen not identified.